Utilização do subproduto do beneficiamento do sisal (Agave sisalana Perrine): desenvolvimento de nanoemulsões cosméticas e avaliação da segurança e eficácia - Barreto, Stella Maria Andrade Gomes (2017)
The processing of the leaves of Agave sisalana provides fiber, with added value for the sisal industry, and the rest of the plant material, known as by-product, is thrown and generates environmental impact. Different applications have been attributed, however, there are no scientific researches that aim to use this product as a cosmetic raw material. The objective of this research was to obtain and characterize polysaccharides-enriched fraction (FrE) from the Agave sisalana by-product of, assess the safety in vitro and in vivo, as well as to evaluate the antioxidant activity in vitro, and then to develop a nanoemulsion with moisturizer effect. From the liquid portion of the by-product obtained the crude extract (EB) and two fractions resulting from extractive process. The EB and the fractions were evaluated for the presence of sugars, proteins and polyphenols. Safety was evaluated by cytotoxicity and phototoxicity in vitro assays using the colorimetric method of Neutral Red. Irritability was evaluated by the primary contact test (patch test). The antioxidant capacity was assessed using the DPPH scavenging tests and molybdenum method. Different systems were obtained by means of pseduodiagrama ternary containing, or not, 0.5% FrE. The selected formulations were submitted to preliminary stability tests and accelerated in different temperatures conditions for a period of 90 days. The moisturizing efficacy was evaluated by water content of the stratum corneum and transepidermal water loss for a period of 5 hours. The samples presented as chemical constituents, sugars, polyphenols and proteins. The FrE showed no phototoxic potential or cytotoxic, and was not irritating to skin of volunteers and can be considered an asset with antioxidant property Nanoemulsion containing 40% oil phase, 50% aqueous phase and 10% surfactants was stable for 90 days.The nanoemulsion was able to significantly increase the water content and maintain skin barrier function after 5 hours from a single application. The fraction obtained from the industrial by-product of Agave sisalana demonstrated a promising profile as raw material for cosmetic skin care with moisturizing and antioxidant capacity, together with the possibility of adding value to industrial waste, reducing the damage caused to the environment by disposing of this material.